Disassembling the Software Architecture of Digital Libraries: Getting More Out of the Building Blocks - Bainbridge, David (Journal of Information and Knowledge, 2019)
This article is the second in a series of three publications that reflect on the boundaries and perceptions of what we think of when we hear the term Digital Libraries, with reference to our mainstream digital library systems. In this second article we look at how the existing building blocks of these digital library software architectures can be re-purposed - with only a modest amount of work - to better support interoperability. We do so through two key developments that show what is possible when this thinking is applied to the open source Greenstone software architecture, supported by several examples of it in use. The first key development focuses on the document ingest phase of the digital library, and shows how it can be transformed into an exchange centre for other digital library systems. The second key development builds on top of the ingest developments of the first, and targets interoperability within the runtime system. It demonstrates how a proxying technique can be used to provide a ready-to-use interactive workflow and end-user experience crafted for one digital library architecture (Greenstone), but applies it to another (Fedora).